1998
DOI: 10.1080/0742-969x.1998.11882904
|View full text |Cite
|
Sign up to set email alerts
|

God and the Search for Meaning Among Hospice Caregivers

Abstract: The purposes of this study were (1) to describe both religious and nonreligious appraisals of caregiving for a terminally ill patient and (2) to explore the relationship between these appraisals with situational outcomes, mental health outcomes, and spiritual health outcomes in the caregivers. Ninety-two caregivers completed a questionnaire consisting of religious and nonreligious appraisals, general and religious outcomes, depression, anxiety, and purpose in life. Caregivers who appraised their situation as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Another meta-analysis of more than 100 studies also revealed that this form of spiritual struggle is positively associated with depressive symptoms (Smith et al 2003). Specific studies have found that divine struggle is correlated with: (a) symptoms of depression and suicidality, anxiety, and low self-esteem among college students and clinical samples (Exline et al 1999;Exline et al 2000); (b) distress and symptoms of post-traumatic stress disorder (PTSD) among victims of the 1993 Midwest floods and members of churches located near the site of the Oklahoma City bombing (Pargament et al 1994;Pargament et al 1998;Smith et al 2000); (c) higher levels of anxiety, phobic anxiety, depression, paranoid ideation, obsessive-compulsive disorder, and somatization in an online national sample of adults (McConnell et al 2006); (d) greater depression, higher perceived burden, and lower sense of meaning and purpose among samples of Alzheimers and hospice caregivers (Mickley et al 1998;Shah et al 2001); (e) slower rates of recovery among medical rehabilitation patients (Fitchett et al 1999); and (f) poorer physical health and increased mortality risk in medically-ill older patients (Pargament et al 2001(Pargament et al , 2004. This body of theory and evidence provides the basis for our first study hypothesis: H1 Troubled relationships with God will be positively associated with psychological distress.…”
Section: Divine Struggles: Troubled Relationships With Godmentioning
confidence: 99%
“…Another meta-analysis of more than 100 studies also revealed that this form of spiritual struggle is positively associated with depressive symptoms (Smith et al 2003). Specific studies have found that divine struggle is correlated with: (a) symptoms of depression and suicidality, anxiety, and low self-esteem among college students and clinical samples (Exline et al 1999;Exline et al 2000); (b) distress and symptoms of post-traumatic stress disorder (PTSD) among victims of the 1993 Midwest floods and members of churches located near the site of the Oklahoma City bombing (Pargament et al 1994;Pargament et al 1998;Smith et al 2000); (c) higher levels of anxiety, phobic anxiety, depression, paranoid ideation, obsessive-compulsive disorder, and somatization in an online national sample of adults (McConnell et al 2006); (d) greater depression, higher perceived burden, and lower sense of meaning and purpose among samples of Alzheimers and hospice caregivers (Mickley et al 1998;Shah et al 2001); (e) slower rates of recovery among medical rehabilitation patients (Fitchett et al 1999); and (f) poorer physical health and increased mortality risk in medically-ill older patients (Pargament et al 2001(Pargament et al , 2004. This body of theory and evidence provides the basis for our first study hypothesis: H1 Troubled relationships with God will be positively associated with psychological distress.…”
Section: Divine Struggles: Troubled Relationships With Godmentioning
confidence: 99%
“…Bush et al, 1999;Koenig, Pargament, & Nielsen, 1998;Mickley, Pargament, Brant, & Hipp, 1998;Pargament, Cole, Vandecreek, Belavich, Brant, & Perez, 1999;Pargament et al, 1990;Thompson & Vardaman, 1997). In contrast, researchers have linked several negative religious coping methods crosssectionally to poorer spiritual, psychological and physical health: spiritual discontent, punitive religious reframing, self-directing religious coping and congregational discontent (e.g.…”
mentioning
confidence: 99%
“…For instance, religious people may appraise their situation as less harmful or threatening, for example by viewing the potentially stressful organizational event (e.g. restructuring, mergers, layoffs) as part of God's plan (Mickley et al, 1998), or as a spiritual opportunity (Pargament, 1997). Furthermore, religious individuals may perceive themselves as more capable of dealing with these events, because they feel supported by God or because of their highly developed sense of spirituality (Dezutter et al, 2010;Probst and Strand, 2010).…”
mentioning
confidence: 99%